THE INFLUENCE OF MALL ON ENHANCING STUDENTS’ LITERACY SKILLS - Margaretha Dharmayanti Harmanto (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2021)
This study investigates the influence of MALL (Mobile Assisted Language Learning) on enhancing students' literacy skills in the international program of accounting. The mobile-phone platforms worked as media of interaction with the students in the learning-teaching and outside the classroom. The mobile phone is used as a medium for practising both reading and writing. This research was a quantitative study using an experimental design. The population of the study was the students of the International Program of Accounting department. The result showed that Sig. (2-tailed) .197 > 0.05 which means there was no significant effect in the use of MALL to enhance the students' literacy skills in general. Instead, the use of MALL has a significant effect in improving the spelling which was Sig. (2-tailed) 0.043 < 0.05, and grammar for the plural and singular parts for Sig. (2-tailed) 0.025<0.05.